Forecasting the instability of Polish banks - Łupiński, Marcin (Publishing House of Wroclaw University of Economics and Business, 2022)
The paper presents a formalised procedure of the identification of financial stability EWI (Early Warning Indicators) for the Polish banking sector, in which a two-step procedure was applied. First, the author used a logit model to estimate of the biggest Polish banks’ probabilities of default (PDs). Next, the calculated individual banks’ PDs were used to prepare aggregated domestic banking system stability. In the last step, employing a set of multivariate Markov-switching models with distributed lags (MMSM-DL), the author applied this measure to identify EWI from the candidate macro, private and public debt, banking sector, financial markets and property prices indicators. The best performing EWI were selected with application of area under the receiver operating characteristic (AUROC) metrics and compared with an output of a popular logistic regression (LR) model. To the best author’s knowledge, this article presents for the first time a fully formalised analytical framework based on the MMSM-DL approach that combines microprudential and macroprudential data for the Polish banks financial stability EWI identification. Moreover, the survey supports the hypothesis that the Polish banking sector is stable with use of a formalised econometric procedure.
Argumenta Oeconomica, 2022, Nr 2 (49), s. 115-134
Keywords: macroprudential analysis; early warning indicators; EWI; Markov-switching models; AUROC; Area Under the Receiver Operating Characteristic